2019
DOI: 10.1016/j.msard.2018.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of dimethyl fumarate versus fingolimod and teriflunomide among MS patients switching from first-generation platform therapies in the US

Abstract: Background: Previous real-world comparative research of MS disease modifying therapies (DMTs) in the overall population has suggested dimethyl fumarate (DMF) to be comparable to fingolimod (FTY) and more efficacious than teriflunomide (TERI) in reducing relapses. However, there is limited comparative evidence in patients switching from platform DMTs in the US. The objective of the study was to compare the annualized relapse rate (ARR) and risk of relapse in MS patients who have switched from a platform therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 36 publications
(48 reference statements)
6
53
0
Order By: Relevance
“…Ontaneda et al, analysed patients from a commercial claims database, switching from platform disease-modifying therapies (DMTs) to DMF, FTY and TERI and staying on treatment for at least 3 months. Comparable post-index ARR were observed between DMF and FTY, but were significantly lower with DMF versus TERI [16]. In contrast, Kalincik et al [17] showed a lower ARR on FTY compared with DMF and TERI analysing 614 (TERI), 782 (DMF) or 2332 (FTY) patients from the global MSBase cohort, staying at least 3 months on treatment.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Ontaneda et al, analysed patients from a commercial claims database, switching from platform disease-modifying therapies (DMTs) to DMF, FTY and TERI and staying on treatment for at least 3 months. Comparable post-index ARR were observed between DMF and FTY, but were significantly lower with DMF versus TERI [16]. In contrast, Kalincik et al [17] showed a lower ARR on FTY compared with DMF and TERI analysing 614 (TERI), 782 (DMF) or 2332 (FTY) patients from the global MSBase cohort, staying at least 3 months on treatment.…”
Section: Discussionmentioning
confidence: 89%
“…The longer observation period on treatment (at least 24 months) produced more robust data especially in regards to disease progression and regression. patients Two previous studies also compared between these oral MS drugs [16,17]. Ontaneda et al, analysed patients from a commercial claims database, switching from platform disease-modifying therapies (DMTs) to DMF, FTY and TERI and staying on treatment for at least 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observational studies have reported inconsistent results regarding clinical MS activity at 1 year (annualized relapse rate, time to first relapse) but none has compared clinical efficacy, MRI disease activity, and treatment withdrawals at 1 and 2 years in a large population of patients. [8][9][10][11][12] Such a study has the advantage of being more representative of real-life practices and effects, even if the treated patients are often noncomparable directly due to indication biases. In this context, taking advantage of the French Multiple Sclerosis Registry (Observatoire Français de la Sclérose En Plaques [OFSEP]), we propose to compare the real-life effectiveness and tolerance of DMF and TRF, using weighted propensity scores to deal with possible confounders.…”
mentioning
confidence: 99%
“…'First-line' or 'platform' agents usually refer to interferons, glatiramer acetate, and teriflunomide, while 'highefficacy' agents usually include fingolimod, alemtuzumab, natalizumab, ocrelizumab, and cladribine tablets [5,12]. Dimethyl fumarate may be intermediate between these categories, as there is some evidence that the efficacy of this agent is similar to that of fingolimod [33,34].…”
Section: Overview Of Dmdsmentioning
confidence: 99%